Pembenahan Perpustakan SMAN 2 Kolaka sebagai Bentuk Kontribusi Mahasiswa PLP 2026 USN Kolaka - La Ilfan Afif Amrullah; A. Ilmadani MGB; Siti Saleha; Anggie Putri Nuraghvy; Anisa; Kartini A. Mbera; Alifiah Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The school library is a vital infrastructure that serves as a literacy center and learning resource for students and teachers. However, the library at SMAN 2 Kolaka is currently poorly maintained, dusty, and its book collection is poorly organized, resulting in few student visits. This activity aims to improve the library to create a comfortable environment for the school community and increase student interest in reading. The activity was carried out periodically from January 23 to 31, 2026, through three main stages: planning, implementation, and evaluation. The implementation phase included a thorough cleaning of the library area to prevent damage to the collection from termites, dismantling and sorting books based on the curriculum (KTSP, K13, and Merdeka Curriculum), and rearranging books on shelves by subject for easy access. The results of this activity showed significant changes in the physical condition of the library, which has become cleaner and more organized. Through the contributions of these 2026 PLP USN Kolaka students, it is hoped that the SMAN 2 Kolaka library can once again function optimally as an educational support facility and school literacy center.